2019
DOI: 10.3390/ma12182989
|View full text |Cite
|
Sign up to set email alerts
|

The Significant Impact of Carbon Nanotubes on the Electrochemical Reactivity of Mg-Bearing Metallic Glasses with High Compressive Strength

Abstract: Here, we elucidate the significant impact of carbon nanotubes (CNTs) on the electrochemical behavior of Mg-based amorphous composite materials that were reinforced with CNTs while using pressure die casting. The addition of 3 vol % CNTs led to an increase in the compressive strength of Mg-based amorphous material from 812 MPa to 1007 MPa, and the fracture strain from 1.91% to 2.67% in the composite. Interestingly, the addition of CNTs significantly contributed to the enhancement of corrosion resistance of Mg-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It is observed that the inclusion of CNTs increases resistance to corrosion by lowering the current density and improving potential [55]. Among the secondary addition to magnesium composites, CNTS are, without hesitation, an excellent choice [56]. CNTs possess poor water wettability and sturdy corrosion resistance; galvanic corrosion is observed between the magnesium matrix and CNTs [57].…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the inclusion of CNTs increases resistance to corrosion by lowering the current density and improving potential [55]. Among the secondary addition to magnesium composites, CNTS are, without hesitation, an excellent choice [56]. CNTs possess poor water wettability and sturdy corrosion resistance; galvanic corrosion is observed between the magnesium matrix and CNTs [57].…”
Section: Resultsmentioning
confidence: 99%
“…Under pressure, the average distance between CNTs is reduced, which reduces the tunneling resistance. [33]Therefore, during the vibration fatigue cycle, as the vibration magnitude increases, the laminate's bending strain continues to increase, and the amplitude of the ΔR/R 0 of the BP sensor also increases significantly. When the damage accumulates and causes microcracks in the substrate of laminate, it will cause CNTs contact fracture, increasing the ΔR/R 0 of BP sensors and cannot return to its original state.…”
Section: The Sensing Mechanism Of Bp Sensor Under Bending Strainmentioning
confidence: 99%